Mid-Term Results of Partial Trapeziectomy and Simple FCR Tendon Graft Interposition in a Selected Group of Patients with Thumb Carpometacarpal Joint Arthritis - Al-Qattan, Mohammad M.; Al Mohrij, Saad A. (Journal of Hand and Microsurgery, 2019)
Introduction There are several surgical options for the treatment of osteoarthritis of the first carpometacarpal joint (CMCJ1). We introduce our technique of partial trapeziectomy and flexor carpi radialis (FCR) tendon graft interposition in a selected group of patients with CMCJ1.Objective The main purpose of this article is to investigate the mid-term results of our technique.Patients and Methods This is a retrospective study of 24 patients with CMCJ1 arthritis (23 females and 1 male with a mean age of 68 years) who were treated with partial trapeziectomy and simple FCR tendon graft interposition. Patient selection for this procedure was based on two prerequisites: the absence of scaphotrapezial arthritis and the absence of severe ligament laxity or severe subluxation of the CMCJ1. All patients had a mean follow-up of 6 years. Pre- and postoperative standard assessments were done.Results There were no postoperative complications and a zero-revision rate. All parameters significantly improved after surgery (p < 0.05). All patients were “very satisfied” with the outcome.Conclusion The procedure of partial trapeziectomy and FCR tendon graft interposition can give an excellent mid-term outcome with a zero-revision rate if utilized in a selected group of patients with CMCJ1 arthritis.
Keywords: results; partial trapeziectomy; tendon graft interposition; first carpometacarpal joint